Pengaruh Media Interaktif Animasi terhadap Minat Belajar Mata Pelajaran IPAS Materi Wujud Zat dan Perubahannya pada Siswa Kelas IV SDN 015 Samarinda Ulu - Martini, Lahai; Makmun; Khotimah, Khusnul; Muhlis (Mataram University, 2026)
This study aimed to examine the effect of using interactive media on the learning interest of fourth-grade students in the subject of Natural and Social Sciences (IPAS), specifically on the topic of states of matter and their changes, at SD Negeri 015 Samarinda Ulu. The research problem was based on students’ low learning interest, which was indicated by limited active involvement during the learning process and a tendency for students to become easily bored when conventional teaching methods were applied. This study employed a quasi-experimental method using a nonequivalent control group design. The research sample consisted of 40 fourth-grade students, divided into an experimental class and a control class, each comprising 20 students. The research instrument was a learning interest questionnaire that had been tested for validity and reliability. Descriptive analysis results showed that the average learning interest of students in the experimental class using animated interactive media reached 65%, while the control class achieved only 50%. Indicator-based analysis revealed that the experimental class experienced improvements in students’ enjoyment, engagement, interest, and attention. The normality test results indicated that the data were normally distributed, and the homogeneity of variance test showed that both sample groups had equal variances. Furthermore, hypothesis testing using an independent samples t-test yielded a significance value of 0.015 (< 0.05), indicating a statistically significant effect. It can be concluded that the use of animated interactive media has a significant effect on increasing fourth-grade students’ learning interest in IPAS, particularly in the aspects of enjoyment, interest, engagement, and attention. Therefore, it is recommended that teachers utilize animated interactive media as an alternative instructional tool, especially for abstract subject matter, to enhance students’ learning interest.